2008
DOI: 10.1016/s1808-8694(15)31374-4
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Listening Test (directed attention mode) in children with cleft lip and palate

Abstract: in the dichotic listening test only the girls with cleft lip and palate had lower scores than the girls in the control group. This is a prospective clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The literature 49 50 51 52 53 54 55 56 57 has grown in the investigation of the evaluation of the central hearing abilities, through questionnaires and behavioral test of the hearing processing in subjects with this kind of malformation. However, it is limited when the evaluation of these abilities is related to speech disorders and to VPD present in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The literature 49 50 51 52 53 54 55 56 57 has grown in the investigation of the evaluation of the central hearing abilities, through questionnaires and behavioral test of the hearing processing in subjects with this kind of malformation. However, it is limited when the evaluation of these abilities is related to speech disorders and to VPD present in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that home intervention through training with simple and easily accessible materials may be an alternative to minimize the deleterious effects of CAPD, especially in populations in which the incidence of central alteration is high as in children with CLP. It worth emphasizing that the training used in this study encompassess the main impaired auditory abilities in children with CLP and CP as reported in the specialized literature 7,[11][12][13][14] and that the exercises proposed are also endorsed in the specialized literature 15 .…”
Section: Introductionmentioning
confidence: 91%
“…A study shows that about 70% of individuals with CLP have CAPD 7 and that the auditory abilities that are mainly affected are figure ground, closure and integration and binaural integration [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Maximino et al [ 23 ▪ ] reported 50% of their cohort failing an attention measure which used words as the target. Lemos and Feniman [ 34 ] used a similar measure and found children with CLP made more errors than their noncleft peers and were significantly more distracted ( P = 0.008). In studies using parent report, parents of children with CLP consistently report difficulties with attention.…”
Section: Recent Findingsmentioning
confidence: 99%